How does climate change affect the food security and vulnerability of women? A systematic review of gender perspectives - Moon, Monira Parvin (Frontiers in Climate, 2024)
In Bangladesh, vulnerable groups including women and food security are severely impacted by climate change. Due to their lack of means for unequal climate adaptation, the impoverished and marginalized in developing countries are more exposed and vulnerable. This research study looks at how Bangladesh's food security and the status of disadvantaged women are affected by climate change. Gender-based vulnerability is rising as a result of expanding catastrophe consequences, such as decreased agricultural productivity, rising costs, joblessness, food insecurity, post-hazardous illnesses, etc., according to the literature review findings. The assessment highlights the significant risks that climate change poses to Bangladesh's food security and vulnerable women, including increased susceptibility to food shortages and postdisaster issues, given that women in Bangladesh are more susceptible to these issues due to their social, economic, and political circumstances. The literature review demonstrates that disadvantaged groups, particularly women, are negatively impacted by climate change. Profound policy implications should propose for enhancing system performance, coordinating regional agricultural output, and fortifying resistance to climate change.